2021
DOI: 10.3390/f12020249
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Modification Treatment on Some Physical and Mechanical Properties of Pinus oocarpa Wood

Abstract: This study deals with the effect of heat treatment on Pinus oocarpa specimens from forest plantations in Colombia. The effects of two heat treatments at 170 and 190 °C for 2.5 h in saturated vapor were evaluated based on the color, dimensional stability, air-dry and basic densities, modulus of elasticity (MOE), and modulus of rupture (MOR) in static bending of samples. The evaluations were carried out following the Colombian Technical Standards NTC 290 and 663, and the color changes resulting from heat treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Won et al [93] observed increased values for thermal treated Pinus densiflora compared to untreated samples. Herrera-Builes et al [91], using specimens of 410 × 25 × 25 mm (L x R x T), found an increase in MOR of about 47 and 22% after thermal modification of wood at 170 and 190 • C, respectively, whereas MOE increased by 4 and 10%, respectively. The authors mentioned that the increase in mechanical properties might have been due to the condensation reactions in lignin and the rearrangement and crystallinity increase of cellulose, which may have acted as a "hardener" [91,94].…”
Section: Modulus Of Elasticity and Modulus Of Rupturementioning
confidence: 98%
See 2 more Smart Citations
“…Won et al [93] observed increased values for thermal treated Pinus densiflora compared to untreated samples. Herrera-Builes et al [91], using specimens of 410 × 25 × 25 mm (L x R x T), found an increase in MOR of about 47 and 22% after thermal modification of wood at 170 and 190 • C, respectively, whereas MOE increased by 4 and 10%, respectively. The authors mentioned that the increase in mechanical properties might have been due to the condensation reactions in lignin and the rearrangement and crystallinity increase of cellulose, which may have acted as a "hardener" [91,94].…”
Section: Modulus Of Elasticity and Modulus Of Rupturementioning
confidence: 98%
“…The results indicate that higher treatment temperature resulted in greater colour changes, with the ∆E* values being about 24 for Thermo-S and about 33/31 for Thermo-D Norway spruce and Scots pine wood. A ∆E* value higher than 6 is classified as a major colour change [90,91].…”
Section: Classmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this kind of research is focused on testing the properties of the top layer and is conducted on separated face layers material (without base layer) or on the face layer as a part of flooring. The research may include exposition to temperature and humidity [7], hardness [8][9][10], strength [11], top-layer examination after material modifications [12][13][14], or in situ polymerization of active monomers [15]. The study of entire flooring materials focuses on connection with heating systems [16][17][18][19][20] or using individual wood species or quality for flooring applications.…”
Section: Introductionmentioning
confidence: 99%
“…Heat treatment is a method of exposing wood to an almost oxygen-free environment under high temperature conditions and causing changes in the chemical structure of the wood substance [4,5]. Hemicellulose first degrades during the heat treatment process, including acid hydrolysis and decarboxylation reactions [6].…”
Section: Introductionmentioning
confidence: 99%